2011
DOI: 10.1111/j.1538-7836.2010.04160.x
|View full text |Cite
|
Sign up to set email alerts
|

In the presence of strong P2Y12 receptor blockade, aspirin provides little additional inhibition of platelet aggregation

Abstract: In the presence of strong P2Y 12 receptor blockade, aspirin provides little additional inhibition of platelet aggregation. J Thromb Haemost 2011; 9: 552-61.Summary. Background: Aspirin and antagonists of platelet ADP P2Y 12 receptors are often coprescribed for protection against thrombotic events. However, blockade of platelet P2Y 12 receptors can inhibit thromboxane A 2 (TXA 2 )-dependent pathways of platelet activation independently of aspirin. Objectives: To assess in vitro whether aspirin adds additional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
107
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(128 citation statements)
references
References 41 publications
14
107
3
4
Order By: Relevance
“…As we have previously reported in standard 96-well plate and optimul kinetic aggregometry [1,[4][5][6], we found that aspirin significantly inhibited ( p < 0.05) aggregation induced by EPI and completely abolished responses to AA and collagen. PAM, however, significantly attenuated ( p < 0.05) aggregation induced by all agonists tested, except for ristocetin, which acts through a process that involves agglutination and not aggregation.…”
supporting
confidence: 84%
“…As we have previously reported in standard 96-well plate and optimul kinetic aggregometry [1,[4][5][6], we found that aspirin significantly inhibited ( p < 0.05) aggregation induced by EPI and completely abolished responses to AA and collagen. PAM, however, significantly attenuated ( p < 0.05) aggregation induced by all agonists tested, except for ristocetin, which acts through a process that involves agglutination and not aggregation.…”
supporting
confidence: 84%
“…In particular, the level of platelet inhibition achieved by combining aspirin and a potent P2Y 12 receptor antagonist is no greater than that produced by the P2Y 12 receptor antagonist alone. 31 Our study confirms these in vitro findings by demonstrating in vivo that potent P2Y 12 receptor blockade with both prasugrel and ticagrelor is also associated with inhibitory effects on measures of non-ADP-induced platelet reactivity. In particular, our study further expands on previous observations showing that, in DM patients, the addition of either prasugrel or ticagrelor on top of aspirin is able to significantly reduce thromboxane A 2 -mediated platelet reactivity, as assessed by assays sensitive to aspirin-induced effects (arachidonic acid-and collageninduced aggregation), and platelet reactivity mediated by thrombin, as well, in both the acute and maintenance phases of treatment.…”
supporting
confidence: 78%
“…The effects of aspirin on platelet reactivity are relatively limited compared with P2Y 12 inhibition. 13 Furthermore, it has been suggested that P2Y 12 inhibition alone may partially inhibit platelet thromboxane A 2 synthesis, 14,15 and in the presence of strong P2Y 12 inhibition, the additional effects of higher aspirin doses may result in a reduction of prostacyclin release, potentially shifting the influence of aspirin to a prothrombotic effect. 16 Consistent with the Clopidogrel Optimal Loading Dose Usage to Reduce Recurrent Events/Optimal Antiplatelet Strategy for Interventions (CURRENT/OASIS 7) trial, 17 no association of aspirin maintenance dose with ischemic event rates in the clopidogrel group was observed.…”
Section: Discussionmentioning
confidence: 99%